Hyperelasticity Primer - Hackett, Robert M. (Springer International Publishing, 2018)
This book introduces the subject of hyperelasticity in a concise manner mainly directed to students of solid mechanics who have a familiarity with continuum mechanics. It focuses on important introductory topics in the field of nonlinear material behavior and presents a number of example problems and solutions to greatly aid the student in mastering the difficulty of the subject and gaining necessary insight. Professor Hackett delineates the concepts and applications of hyperelasticity in such a way that a new student of the subject can absorb the intricate details without having to wade through excessively complicated formulations. The book further presents significant review material on intricately related subjects such as tensor calculus and introduces some new formulations. Introduces hyperelasticity in a concise, straightforward manner using practical examples; Reinforces understanding with a significant number of example problems/solutions to demonstrate application of the presented formulations; Defines material models for rubber, polymers, foams and soft tissue; Emphasizes incremental formulations and solutions; Presents material related to finite element implementation and incremental finite viscoelasticity; Explains methodology of obtaining model parameters from test data.